Biodegradability of corn starch films containing nanocellulose fiber and thymol - Nordin, Norhazirah; Fisal, Muhamad Farhan; Othman, Siti Hajar; Mohamed Amin Tawakkal, Intan Syafinaz; Kadir Basha, Roseliza (Walter de Gruyter, 2024)
The biodegradability of corn starch (CS), CS/nanocellulose fiber (NCF), and CS/NCF/thymol (Thy) films produced via a solvent casting method was investigated by soil burial test (SBT) in two types of soils (compost and planting). The films were evaluated in regard to weight loss, visual appearance, morphological properties, and structural properties. Based on SBT, CS/NCF films exhibited the least weight loss and changes in visual appearance, morphology, and structural properties. The inclusion of Thy into CS/NCF films increased substantially the degree of degradation of films in both soils. The microscopy images of films after SBT show that all of the films had voids, holes, and rough surfaces especially films containing Thy, indicating that the films degraded. Fourier-transform infrared spectroscopy results revealed shifting of peaks and changes in peak intensity of some functional groups of films, confirming the degradation phenomenon. Compost soil has more organic material, active microbes, nutrients, and humidity than planting soil, thus resulting in films with greater weight loss and changes in visual appearance, morphology, and structural properties. It can be concluded that the films have a high potential for applications and can help to lower the amount of usage of non-degradable materials.